Corporate image : the strategic imperative in the Nigerian banking sector - Ogundipe, Victor Akinloye (Lagos, Nigeria : Newswatch communications, 1988)
This book attempts to harness the experiences of the author, in the context of the vantage position which he occupied as public relations manager of International Bank for West Africa Limited over a very eventful three-year period.
ijb, 18/01/2019
Loans
Keywords: Corporations; Banks and banking; Nigeria